Carbonized rice husk and cocopeat as alternative media bed for aquaponic system - Muhd Nazrul Hisham Zainal Alam,; Nur Syahmi Izzati Ali Othman,; Sani Amril Samsudin,; Anwar Johari,; Mimi Haryani Hassim,; Mohd Johari Kamaruddin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study evaluates the suitability of carbonized rice husk and cocopeat substrates as alternative media bed in aquaponics unit for cultivation of red Nile tilapia and Gynura procumbens. Area occupied by the aquaponics unit is about 4.5 m2 and it was operated under equatorial climate conditions. Various substrates namely lightweight expanded clay aggregate (LECA), cocopeat, carbonized rice husk and a mixture of cocopeat-rice husk at ratio 1:1 were prepared using polybags for growing of the longevity spinach. The resultant effects from fish cultivation and plants growth on the water qualities and nitrification efficiency of the aquaponics unit were reported. The aquaponics unit were operated for twelve weeks and the values of pH, temperature, and dissolved oxygen level were measured to be within the range of 6.4-6.9, 27.7-29oC, and 5.5-7 mg·L-1, respectively. Survival rate for fish was 98% with specific growth rate (SGR) and food conversion ratio (FCR) of 6.9% per day and 1.13, respectively. Nutrient deficiency was not evident and plants showed healthy growth with harvest yield ranging between 3.6 and 3.9 kg·m-2. Results attained signified the suitability of utilizing carbonized rice husk and cocopeat as alternatives media bed compared to commercial media bed such as LECA.